PENGARUH PENGELUARAN INVESTASI PEMERINTAH DAERAH DAN INVESTASI SWASTA TERHADAP PERTUMBUHAN PDRB PER KAPITA DI INDONESIA (Studi Kasus Konvergensi Sebelum dan Selama Otonomi Daerah) - , YOZI AULIA RAHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research have two aimed, first to identified convergence of GRDP per capita in Indonesia before and during regional autonomy. Second, to analyzed the impact of regional government investment expenditure and private investment to growth of GRDP per capita in Indonesia before and during regional autonomy. This research used panel data 26 province with time period 1990-2010. The analysis of absolute convergence used common effect model and conditional convergence used fixed effect model. The results shows absolute convergence and conditional convergence are happened in Indonesia before and during regional autonomy. regional government investment expenditure is not significant, meanwhile private investment is significant to growth of GRDP per capita in Indonesia before regional autonomy. During regional autonomy, regional government investment expenditure and private investment are significant to growth of GRDP per capita in Indonesia.